Lipid Droplet Proteins in Acne Skin: A Sound Target for the Maintenance of Low Comedogenic Sebum and Acne-Prone Skin Health - Olivier Sorg; Thérèse Nocera; Fabienne Fontao; Nathalie Castex-Rizzi; Lucile Garidou; Christophe Lauze; Jimmy Le Digabel; Gwendal Josse; Jean-Hilaire Saurat (Elsevier, 2021)
In adipocytes and sebocytes, lipid droplet proteins control the storage of lipids in organized droplets and their release on demand. The contribution of lipid droplet proteins to the pathogenesis of acne is plausible because they control the levels of comedogenic free fatty acids. The expression of two lipid droplet proteins, CIDEA and PLIN2, was analyzed in the skin of patients with acne by immunohistochemistry and western blotting. The design of clinical protocols allowed correlating the expression of CIDEA and PLIN2 with both comedogenesis and the release of free fatty acids. Both proteins were detected by immunohistochemistry in the sebaceous glands of patients with acne, with a disturbed expression pattern of PLIN2 compared with that in the controls. Higher levels of PLIN2 and CIDEA, as detected by western blotting in the infundibulum, significantly correlated with lower ongoing comedogenesis over 48 weeks of Silybum marianum fruit extract application. Accordingly, free fatty acid release from sebum triglycerides was significantly decreased, as shown with two distinct methods. The data are consistent with the expected role of PLIN2 and CIDEA in the prevention of comedogenic free fatty acid release. Modulation of PLIN2 and CIDEA expression appears as a sound target for the maintenance of low comedogenic sebum and acne-prone skin health.